Cover Image, Volume 10, Issue 6. (18th October 2018) - Miller, Michael I.; Arguillère, Sylvain; Tward, Daniel J.; Younes, Laurent
Abstract : The cover image is based on Advanced Review Computational anatomy and diffeomorphometry: A dynamical systems model of neuroanatomy in the soft condensed matter continuum by Michael I. Miller et al., DOI: 10.1002/wsbm.1425 . Abstract : The cover image is based on Advanced Review Computational anatomy and diffeomorphometry: A dynamical systems model of neuroanatomy in the soft condensed matter continuum by Michael I. Miller et al., DOI: 10.1002/wsbm.1425 .